'The Bricks and Mortar of All Policy Areas Which Concern Government': Statistics and the Labour Force Survey at its UK Origins. Issue 2 (1st July 2022) - Arch, Linda
Abstract : On 1 January 1973, the UK joined the European Economic Community and, in its capacity as a member state, conducted a Labour Force Survey in that year for the first time. The purpose of this article is to contribute to the history of the Labour Force Survey. It begins by outlining the landscape of government statistics in the UK in the post-Second World War period. It then explores the UK's decision in June 1972 to participate in the survey, with a particular focus on the deliberations of the working group of government statisticians tasked with implementing the survey. It identifies the key issues with which the working group grappled. It draws attention to the economic narratives which prevailed and suggests that decisions relating to the collection, analysis, and interpretation of data, and their publication as official statistics, may be influenced by the dominant narratives. In the final section, it describes how the UK implemented the survey, and identifies the ways in which the UK's approach to the implementation of the survey differed from those of other member states. This research is an empirical study based upon the analysis of primary and secondary sources (both published records and unpublished records in archives).